Concordance between inflammation at physical examination and on MRI in patients with early arthritis. Issue 3 (12th December 2013) - Krabben, A; Stomp, W; Huizinga, T W J; van der Heijde, D; Bloem, J L; Reijnierse, M; van der Helm-van Mil, A H M
Abstract : Background: MRI is increasingly used to measure inflammation in rheumatoid arthritis (RA) research, but the correlation to clinical assessment is unexplored. This study determined the association and concordance between inflammation of small joints measured with MRI and physical examination. Methods: 179 patients with early arthritis underwent a 68 tender joint count and 66 swollen joint count and 1.5T MRI of MCP (2–5), wrist and MTP (1–5) joints at the most painful side. Two readers scored synovitis and bone marrow oedema (BME) according to the OMERACT RA MRI scoring method and assessed tenosynovitis. The MRI data were first analysed continuously and then dichotomised to analyse the concordance with inflammation at joint examination. Results: 1790 joints of 179 patients were studied. Synovitis and tenosynovitis on MRI were independently associated with clinical swelling, in contrast to BME. In 86% of the swollen MCP joints and in 92% of the swollen wrist joints any inflammation on MRI was present. In 27% of the non-swollen MCP joints and in 66% of the non-swollen wrist joints any MRI inflammation was present. Vice versa, of all MCP, wrist and MTP joints with inflammation on MRI 64%, 61% and 77%, respectively, were not swollen. BME, also in case of severe lesions, occurred frequently in clinically non-swollen joints. Similar results were observed for joint tenderness. Conclusions: Inflammation on MRI is not only present in clinically swollen but also in non-swollen joints. In particular BME occurred in clinically non-inflamed joints. The relevance of subclinical inflammation for the disease course is a subject for further studies.